Manufacture of a Horizontal Double-Screw Mixer for Fermented Feed Production with a 100 kg Batch Capacity - Darianto, Darianto; Hermanto, Tino; Rahmad Aldori, Yopan; Iswandi, Iswandi; Hermawan, Indra; Idris, Muhammad; Jufrizal, Jufrizal; Ariyudha, Andhika (Universitas Medan Area, 2025)
In general, every livestock needs feed in the form of a mixture of livestock feed. The livestock feed fermentation process is currently phenomenal because it provides benefits that are felt by farmers. Maybe many people know the fermentation as a process of making supplement drinks only. It turns out not, the fermentation process can be used as an alternative to making high-quality livestock feed. In addition to being very simple to make, making feed by fermentation also saves time and money, because farmers are no longer busy with herding or grazing. This horizontal mixer machine has a capacity of 100 kg / Batch. In making this machine includes manufacturing processes such as: welding, grinding, drilling, bending, cutting torch or gas cutting, and non-permanent joints, namely nut and bolt joints. The components of the machine are: frame, tube, double screw, axle shaft, bossing, gear box, housing bearing, block bearing, pulley, v-belt, and electric motor. And then assembled and put together into a machine. From the above explanation, the following conclusions can be drawn: 1. Horizontal mixer machine with a tube diameter of 60 cm and a width of 90 cm, is capable of mixing 100 kg/batch of animal feed. 2. Horizontal mixer machine using a double screw produces a more homogeneous mixture compared to using the manual method.